Prevalence of Anemia in Females with Diabetes Mellitus Type-II and Menopausal Females of Hyderabad, Sindh - Ansari, Shafaq; Warsi, Jamshed; Laghari, Zulfiqar (Journal of Liaquat University of Medical & Health Sciences, 2020)
Objective: To determine the prevalence of anemia, in menstruating normal, menstruating diabetic, menopausal normal, menopausal diabetic female. Methodology: A comparative cross sectional study performed at the department of Physiology, Sindh University Jamshoro, from April-September 2019 in collaboration with Liaquat University Hospital Jamshoro/ Hyderabad. The diabetic females recruited from Liaquat medical hospital (LUH) Jamshoro/Hyderabad and menopausal women of society after approval from the research ethical committee of institute. Random sampling technique was chosen for the study. After observing inclusion and exclusion criteria, total 200 females were included in this study. After explaining the purpose of study, verbal and written consent taken, complete blood picture (CBC) performed from all participants. Data was entered in excel sheet and in SPSS 21.0 version. Chi-square test applied. Results: The prevalence of anemia in menstruating normal, menstruating diabetics, menopausal normal, menopausal diabetic was reported 50.00%, 51.67%, 52.00% and 70.00% respectively. The highest prevalence was reported in menopausal diabetic female (70%). Conclusion: The study concludes that the prevalence of anemia in menopausal diabetic is more pronounced than in the other three study groups that are normal menstruating, diabetic menstruating and normal menopausal females. This is suggestive that cessation of menstruation added with diabeties is high risk factor for anemia.